Adalimumab for interleukin‐1β‐mediated chronic non‐scarring scalp folliculitis: Case report and literature review. Issue 1 (2nd September 2021) - Soglia, Simone; Maione, Vincenzo; Bugatti, Mattia; Vermi, William; Calzavara‐Pinton, Piergiacomo; Venturini, Marina
Abstract: Chronic non‐scarring scalp folliculitis is a little‐known entity included within the spectrum of scalp folliculitis, a group of diseases sharing clinical features but with heterogeneity in terms of residual scarring (always absent in chronic non‐scarring scalp folliculitis), microbiology, and response to antibiotics. Chronic non‐scarring scalp folliculitis is most likely an inflammatory disease within the group of neutrophilic dermatoses. The recognition of the inflammatory nature of this disease may pave the way for the use of new therapies, directly targeting pathogenic molecules. Herein, we report the first case of chronic non‐scarring scalp folliculitis treated by adalimumab.